Asymmetric foreign exchange cash flow exposure: A firm-level analysis - Krapl, Alain A. (Journal of Corporate Finance, 2017)
This study analyzes foreign exchange (FX) cash flow and equity exposures of a sample of U.S. multinational firms. Focusing on asymmetry in FX cash flow exposures to direction and magnitude of FX shocks, the study finds that asymmetry is pervasive in several alternative measures of FX cash flow exposure. Also, after decomposing FX equity exposures into discount rate and cash flow components, the study documents significant asymmetries in FX discount rate exposures. The latter finding implies that market-related factors in addition to cash flow–based arguments need to be considered when further exploring FX equity exposure. This study also highlights the importance of model specification: models with asymmetric specifications detect more firms with significant FX exposures.